Some results of researches on pacific herring in the northwestern Bering Sea in 2010-2015 - Sergey V. Loboda; Alexander Yu. Zhigalin (Известия ТИНРО)
The data of pelagic and bottom surveys on pacific herring in the northwestern Bering Sea obtained in 2010-2015 and its stock assessments by different methods are compared. Some biological parameters of the herring are presented and its spatial distribution and migrations are described. The pelagic surveys with stepped trawling and the bottom trawl surveys are concluded as the best for the herring stock assessment and biological characteristic. The stock state in the 2010-2015 is determined as high abundant due to mass migration of herring from the eastern Bering Sea to its northwestern part that starts in June under certain oceanographic conditions. Different modes of the herring feeding migration are revealed for periods of its high and low stock. The results are used for the herring fishery regulation in the northwestern Bering Sea.